Aerobic Acyloxylation of Allylic C−H Bonds Initiated by a Pd0 Precatalyst with 4, 5‐Diazafluoren‐9‐one as an Ancillary Ligand. Issue 13 (5th June 2019) - Kozack, Caitlin V.; Sowin, Jennifer A.; Jaworski, Jonathan N.; Iosub, Andrei V.; Stahl, Shannon S.
Abstract: Palladium‐catalyzed allylic C−H oxidation has been widely studied, but most precedents use acetic acid as the coupling partner. In this study, a method compatible with diverse carboxylic acid partners has been developed. Use of a Pd 0 precatalyst under aerobic reaction conditions leads to oxidation of Pd 0 by O2 in the presence of the desired carboxylic acid to generate a Pd II dicarboxylate that promotes acyloxylation of the allylic C−H bond. Good‐to‐excellent yields are obtained with a roughly 1:1 ratio of the alkene and carboxylic acid reagents. Optimized reaction conditions employ 4, 5‐diazafluoren‐9‐one (DAF) as a ligand, in combination with a quinone/iron phthalocyanine cocatalyst system to support aerobic catalytic turnover. Abstract : Coupling with carboxylates : Use of a palladium(0) precatalyst provides the basis for in situ generation of an active palladium(II) dicarboxylate catalyst under aerobic conditions in the presence of 4, 5‐diazafluoren‐9‐one (DAF). This tactic has been applied to allylic acyloxylation, enabling the formation of allylic esters with diverse nucleophilic carboxylate coupling partners from terminal linear alkenes and cyclic alkenes.